ANALISIS KASUS PEMERASAN DAN DAMPAKNYA TERHADAP KORBAN - Mohamad Ikbal Kadir; Magvira Limu; Putri Yulandari L. Mangambali (Akademika : Jurnal Ilmiah Media Publikasi Ilmu Pengetahuan dan Teknologi, 2026)
Extortion is a criminal act that continues to develop along with social changes and advancements in information technology. This crime not only causes economic losses but also affects the psychological and social conditions of victims. This study aims to analyze extortion cases and examine the impacts experienced by victims from psychological, social, and economic aspects. This research employed a qualitative approach with a case study method. Data were collected through documentation studies, literature reviews, and analysis of several extortion cases occurring in society. Data analysis techniques were conducted descriptively and analytically by categorizing findings based on the forms of extortion and the impacts experienced by victims. The results indicate that victims of extortion experience psychological pressure such as fear, anxiety, stress, and prolonged trauma. In addition, victims also experience social impacts in the form of reduced social interaction, loss of trust in their environment, and feelings of shame that discourage them from reporting the incidents. From an economic perspective, victims suffer financial losses that in some cases affect the economic condition of their families. This study also found that low legal literacy, weak supervision, and misuse of technology contribute to the increasing number of extortion cases, particularly digital-based extortion. Therefore, comprehensive efforts are needed through strict law enforcement, increased public education, and psychological assistance services for victims